BIOCLIMATIC SANCTUARY : KONSERVASI DAN WISATA SERANGGA DI RAGUNAN JAKARTA SELATAN - Nabila, Nabila; Kasimun, Petrus Rudi (Jurusan Arsitektur dan Perencanaan, 2025)
Climate change has had a serious impact on the balance of the ecosystem in Jakarta, especially for pollinating insects such as bees, butterflies, and beetles. Data from BMKG shows that Indonesia's average temperature increased to 27.0°C in 2021, higher than the average temperature for the 1981–2010 period of 26.6°C. In the Jakarta area, the dominance of built-up land causes an increase in surface temperature of 2–5°C, exacerbated by erratic rainfall patterns and increasing frequency of extreme rain. This condition causes pollinating insects to lose their natural habitat, triggering insect urbanization characterized by forced migration or drastic population decline. To address this problem, the Bioclimatic Sanctuary project was designed to provide comfortable and sustainable microhabitats for pollinating insects in urban areas. The design of this project refers to a literature review of bioclimatic principles and applies a regenerative architecture approach that focuses on ecosystem restoration. The Bioclimatic Sanctuary design combines a HEPA ventilation system, vertical gardens, water ponds, energy-efficient lighting, rainwater harvesting, and flowering plants as natural food sources. Shade spaces and vegetation zones are designed to create a stable microclimate. Overall, the Bioclimatic Sanctuary functions as a conservation, education, and regeneration space that supports the preservation of biodiversity, builds ecological awareness in the community, and strengthens food security through the protection of pollinating insects amidst the challenges of climate change. Keywords: bioclimatic; ecosystem; green open space development; insects; regenerative Abstrak Perubahan iklim telah memberikan dampak serius terhadap keseimbangan ekosistem di Jakarta, terutama bagi serangga penyerbuk seperti lebah, kupu-kupu, dan kumbang. Data dari BMKG menunjukkan bahwa suhu rata-rata Indonesia meningkat menjadi 27,0°C pada tahun 2021, lebih tinggi dibandingkan suhu rata-rata periode 1981–2010 sebesar 26,6°C. Di wilayah Jakarta, dominasi lahan terbangun menyebabkan peningkatan suhu permukaan sebesar 2–5°C, diperparah oleh pola curah hujan yang tidak menentu dan meningkatnya frekuensi hujan ekstrem. Kondisi ini menyebabkan serangga penyerbuk kehilangan habitat alaminya, memicu urbanisasi serangga yang ditandai dengan migrasi paksa atau penurunan populasi yang drastis. Untuk mengatasi masalah ini, proyek Suaka Bioklimatik dirancang dengan tujuan menyediakan mikrohabitat yang nyaman dan berkelanjutan bagi serangga penyerbuk di wilayah perkotaan. Perancangan proyek ini mengacu pada kajian pustaka prinsip-prinsip bioklimatik dan menerapkan pendekatan arsitektur regeneratif yang berfokus pada pemulihan ekosistem. Desain Suaka Bioklimatik menggabungkan sistem ventilasi HEPA, taman vertikal, kolam air, pencahayaan hemat energi, pemanenan air hujan, dan tanaman berbunga sebagai sumber makanan alami. Ruang teduh dan zona vegetasi dirancang untuk menciptakan iklim mikro yang stabil. Secara keseluruhan, Suaka Bioklimatik berfungsi sebagai ruang konservasi, pendidikan, dan regenerasi yang mendukung pelestarian keanekaragaman hayati, membangun kesadaran ekologis di masyarakat, dan memperkuat ketahanan pangan melalui perlindungan serangga penyerbuk di tengah tantangan perubahan iklim.